Baking 'crumbly' carbon nitrides with improved photocatalytic properties using ammonium chloride. Issue 4 (4th January 2016) - Savateev, Aleksandr; Chen, Zu Peng; Dontsova, Dariya
Abstract : Ammonium chloride serves as a green, unreactive and reusable template to prepare carbon nitrides with enhanced photocatalytic activity. Abstract : Ammonium chloride can serve as a green, unreactive and reusable template to prepare heptazine-based graphitic carbon nitrides with surface areas up to 30 m 2 g −1 and up to 6 times higher photocatalytic activity, by a simplified procedure that comprises only pyrolysis of the reaction mixture containing precursor and salt.